Sudden unexpected death study underlines risks of infants sleeping in sitting devices. (30th December 2013) - Freyne, B; Hamilton, K; Mc Garvey, C; Shannon, Brenda; Matthews, TG; Nicholson, AJ
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="apa12488-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>